2016
DOI: 10.3892/ol.2016.4097
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Foxc2 enhances apoptosis induced by 5-fluorouracil through activation of MAPK and AKT pathways in colorectal cancer

Abstract: Abstract. The chemotherapy drug 5-fluorouracil (5-FU) is fundamental for the treatment of colorectal cancer (CRC); however, drug resistance to 5-FU may occasionally occur. Abnormal expression of Forkhead box C2 gene (Foxc2) has been identified in several human cancers, but the role of Foxc2 in the progression of CRC remains unclear. The present study established a stable Foxc2-short hairpin (sh)RNA cell line, which was confirmed by western blot analysis and quantitative polymerase chain reaction. The Foxc2-shR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…23,24 As we observed, the sensitivity of MDA-MB-231/CR cells to DOX, TRAIL, and 5-FU was also reduced significantly compared with their parental MDA-MB-231 cells. And similarly, we found the MDA-MB-231/DR cells were resistant to CDDP, TRAIL, and 5-FU (Figure3(a)).…”
Section: Cross-resistance Of Trail and 5-fu In The Cddp/dox-resistantsupporting
confidence: 56%
“…23,24 As we observed, the sensitivity of MDA-MB-231/CR cells to DOX, TRAIL, and 5-FU was also reduced significantly compared with their parental MDA-MB-231 cells. And similarly, we found the MDA-MB-231/DR cells were resistant to CDDP, TRAIL, and 5-FU (Figure3(a)).…”
Section: Cross-resistance Of Trail and 5-fu In The Cddp/dox-resistantsupporting
confidence: 56%
“…It has also been shown to drive osteosarcoma metastasis to lung tissue via a CXCR4-dependent mechanism (26). A large body of evidence has also recently demonstrated that FOXC2 promotes drug resistance in various cancer types, including osteosarcoma, nasopharyngeal carcinoma, and non-small cell lung, prostate, ovarian, colorectal, and basal-like breast cancers (16,18,19,(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…proliferation, epithelial-mesenchymal transition (EMT), metastatic behavior, and drug resistance (10,11,(15)(16)(17)(18)(19). Despite the significance of these oncogenic functions of FOXC2, however, much remains to be learned about the mechanisms underlying their induction.…”
mentioning
confidence: 99%
“…Zhou et al showed that FOXC2 could promote chemoresistance in nasopharyngeal carcinomas via induction of epithelial mesenchymal transition [31]. Also, Yang et al reported that downregulation of Foxc2 could enhance apoptosis induced by 5-fluorouracil in colorectal cancer [32]. Although overexpressed FOXC2 is reported to enhance the epithelial-to-mesenchymal transition and invasion of ovarian cancer cells, the roles of FOXC2 in the development of CDDP resistance in ovarian cancer cells is unclear and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Also, FOXC2 enhanced AKT activity with subsequent GSK-3β phosphorylation and Snail stabilization, and then induced EMT and promoted tumor invasion and metastasis in colorectal cancer [34]. Yang et al showed that downregulation of FOXC2 could enhance 5-fluorouracil-inducing apoptosis through activation of MAPK and AKT pathways in colorectal cancer [32]. However, whether FOXC2 promotes the chemoresistance of ovarian cancer cells to CDDP by activation of Akt and MAPK signaling pathways is unknown.…”
Section: Discussionmentioning
confidence: 99%